Paternal involvement: The central role of fathers in managing children’s emotions - Purwani, Annisa; Hasanah, Iis Uswatun (Aṭfālunā Journal of Islamic Early Childhood Education, 2023)
Emotional development in early childhood plays a vital role in forming the basis of psychological well-being. Father involvement is one of the main factors in the family to manage children emotions. This study aims to determine the central role of fathers in managing early childhood emotions. The research method used in the study was a qualitative case study design. The research subjects involved four fathers who have early childhood. Data was collected through interviews and observation. The results show that the father's involvement is not only limited to the physical aspect but also has a solid contribution to the emotional aspect of the child. It can be concluded that emotional management in early childhood requires holistic attention from fathers. The four fathers had different views and strategies. Some values often emerged as the main focus, including open communication, empathy, combining skills with emotional gentleness, and providing emotional support. The implications can serve as a foundation for fathers' parenting in early childhood and can be enriched to include understanding and emphasizing fathers' involvement in early childhood emotional development. It can guide ECE educators to integrate fathers in learning activities, opening insights on strategies for managing early childhood emotions and the values fathers apply in managing children's emotions.